Bhabinkamtibmas as Panacea in Treating Pathology in Public Organizations - Chairuddin, M Awal; Syam, Husain; Akib, Haedar; Gani, Hamsu Abdul; Rifdan, Rifdan (Universitas Negeri Makassar, 2023)
Harmony based on security, order, and community obedience is an expensive and rare public good in several regions and organizations which is created by every government institution as part of its role in providing basic services for all citizens. Conversely, disharmony or disorder is an organizational (bureaucratic) pathology that needs to be treated by revitalizing the role of public institutions that are competent in this field. The article resulting from this research aims to explain the role of Bhabinkamtibmas as a panacea - for all diseases - in treating the pathology of public organizations. Data, information, and knowledge about the focus of the research at its locus were obtained through observations of various activities, online questionnaires to technologically savvy respondents, interviews with informants, and documentation of the activities of individuals and public institutions involving the role of Bhabinkamtibmas. The analysis technique follows an interactive model, namely data collection, data condensation, data presentation, verification using the Important Performance Analysis (IPA) technique, and conclusions. The results of the research found that Bhabinkamtibmas individually and institutionally play a role in treating (overcoming) various types of organizational (bureaucratic) pathology that disrupt security, order, and community obedience to the research locus. The pathology of public organizations underlies the need to revitalize the role of individuals and institutions of Bhabinkamtibmas while strengthening the assumption about the urgency of public policy as a choice for the government to act or not act in treating the pathology of public organizations through revitalizing the role of Bhabinkamtibmas in overcoming disturbances in security, order and public disobedience. Thus, Bhabinkamtibmas is recognized as a panacea in treating organizational pathology to create harmony based on security, order and community obedience.